Peran Etika Bisnis dalam Membangun Budaya Kerja yang Bertanggung Jawab - Deva Jakaria Sinaga; Fiesto De Limawan; Francois Louis; Susan Grace Nainggolan (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2026)
This study aims to analyze the role of business ethics in building a responsible work culture at PT. Sinergi Karsa Utama (PT. SKU). A qualitative case study approach was used, involving in-depth interviews with leaders and key employees, as well as participant observation. The results indicate that business ethics serves as a "normative bridge and cultural catalyst" that successfully transforms moral values ​​into institutionalized behavior. The implementation of ethics at PT. SKU is a strategic combination of a compliance approach, manifested through a Code of Ethics and Standard Operating Procedures, and an integrity approach driven by the internalization of values.Three key findings confirm the central role of ethics: (1) Ethics as a Normative Anchor: Deeply rooted moral standards lead employees to act responsibly, even without supervision (default behavior), as confirmed by findings of high ownership and a shift from a blaming culture to a learning culture. (2) Ethical Leadership as an Example: Leadership's consistency in integrity and rejection of bribery creates a safe Ethical Climate and builds trust, which is the psychological foundation for accountability. (3) Consistent Enforcement: Fair enforcement mechanisms without double standards create a perception of Procedural Justice (Colquitt, 2001), which strengthens loyalty and a culture of responsibility.Managerial implications indicate that a focus on integrity-based ethics and consistent enforcement is crucial. Empirically, the significant reduction in customer complaint rates (40% in one year) demonstrates the effectiveness of a responsible culture built on a robust ethical framework. This research contributes to the literature by enriching the case study on the causal relationship between business ethics and organizational culture in the context of Indonesian companies